Out-of-plane compressive performance and energy absorption of multi-layer graded sinusoidal corrugated sandwich panels. (15th September 2019) - Zhang, Zhong; Lei, Hongshuai; Xu, Mengchuan; Hua, Jian; Li, Chuanlei; Fang, Daining
Abstract: Corrugated sandwich panels with outstanding load-bearing and energy absorption capacities are widely used in aerospace, naval and automobile industries. Herein, a series of modified sinusoidal corrugated (MSC) sandwich panels, with multiple layers and gradient design, are developed and fabricated by additive manufacturing. An analytical model for quasi-static compression performance was established by using Timoshenko beam and plastic hinge theory. Corresponding experiments and finite element analysis are conducted to investigate the out-of-plane compressive failure mechanism and mechanical performance. The energy absorption capability of graded MSC sandwich panels is studied to reveal the influence of gradient design. The results reveal that the proposed analytical model can accurately predict the compressive modulus and ultimate strength of multi-layer MSC sandwich panels with a maximum deviation of <25%. The introduction of gradient design decreases the initial peak strength and the undulation of load-carrying capacity during nonlinear deformation. The energy absorption ratio slightly increased due to the improved energy absorption process, which can be attributed to the controllable deformation behavior of sandwich core. Graphical abstract: Unlabelled Image Highlights: Gradient design was introduced into the multi-layer sandwich panels consisting of modified sinusoidal corrugated cells. Analytical models were proposed to predict the compressive modulus and strength with higher precision. Deformation behavior and energy absorption of graded panels were investigated by experiment and FEA methods. Multi-layer graded sandwich panel exhibited controllable deformation characteristic and higher energy absorption ratio.